Analisis Kepatuhan Syariah pada Bank Syariah: Studi Kasus Bank Pembiayaan Rakyat Syariah - Aini Maslihatin; Riduwan Riduwan (Jurnal Maps (Manajemen Perbankan Syariah), 2020)
Sharia compliance is the adherence of Islamic banks to Islamic rules or laws in muamalah and is one of the factors that differentiate it from conventional banks. Therefore sharia compliance is a fundamental principle in Islamic banking practices. Muamalah law, especially the economy, has a high degree of difference, so the sharia compliance standards in Indonesia refer to the Fatwa of the National Sharia Council-Indonesian Ulama Council (DSN-MUI). This study aims to analyze the practice of sharia compliance in Islamic Rural Banks (BPRS) in Indonesia. The data analyzed is the assessment of the Sharia Supervisory Board (DPS) on the practice of BPRS for five years. The sample distribution covers all regions of Indonesia with 24 units of analysi with 46 respondenss. The data analysis used quantitative descriptive analysis and compared it with the DSN-MUI fatwa. This study's results indicate that the level of compliance with Islamic rural banks in Indonesia is, on average, excellent. Other findings show that, when viewed from the contract's practice, financing with a musyarakah contract has the highest level of sharia compliance compared to separate agreements. Meanwhile, the lowest sharia compliance is in the murabahah contract. This condition is influenced because Islamic banks often use the murabahah bil wakalah contract. The weakness of this contract lies in the procurement of goods by customers, often not accompanied by proof of purchase.